Automated detection and classification of osteolytic lesions in panoramic radiographs using CNNs and vision transformers - Nistelrooij, Niels van; Ghanad, Iman; Bigdeli, Amir Khosrow; Thiem, Daniel G. E.; von See, Constantin; Rendenbach, Carsten; Maistreli, Ira; Xi, Tong; Bergé, Stefaan; Heiland, Max; Vinayahalingam, Shankeeth; Gaudin, Robert (BMC oral health, 2025)
Diseases underlying osteolytic lesions in jaws are characterized by the absorption of bone tissue and are often asymptomatic, delaying their diagnosis. Well-defined lesions (benign cyst-like lesions) and ill-defined lesions (osteomyelitis or malignancy) can be detected early in a panoramic radiograph (PR) by an experienced examiner, but most dentists lack appropriate training. To support dentists, this study aimed to develop and evaluate deep learning models for the detection of osteolytic lesions in PRs.